The effects of scandalization in political news messages on political trust and message evaluation. (October 2021) - Graβl, Paul; Schaap, Gabi; Spagnuolo, Flavia; Van 't Riet, Jonathan
Recent decades have seen an increase in the frequency of 'scandalization' in political news, a practice in which journalists try to persuade the public that there is a scandal, sometimes by exaggerating the importance of minor mistakes or improprieties. At the moment, little is known about the effects of this practice on news consumers. In this study, we investigated the effects of scandalization on news consumers' evaluations of the politician involved in the scandal, as well as the news message itself. We expected that such responses would be contingent on the perceived severity of the alleged transgression. We conducted an experiment in which we randomized participants (128 undergraduate students at a Dutch university) into a 2(mild versus severe transgression) X 2(scandalization versus control) between participants design. The results showed that, in the mild transgression condition, a scandalizing message caused participants to perceive the alleged events as less serious than a control message, and that scandalization resulted in lower levels of perceived message appropriateness and message trust. No effects of scandalization were found in the severe transgression condition. We conclude that scandalization does not inevitably lead to lower levels of political trust and increased political cynicism. It can, however, lead to lower levels of trust in news reporting when the transgression is seen as mild.